2015
DOI: 10.1103/physrevd.92.124064
|View full text |Cite
|
Sign up to set email alerts
|

Separability of test fields equations on theC-metric background

Abstract: In the Kerr -Newman spacetime the Teukolsky master equation, governing the fundamental test fields, is of great importance. We derive an analogous master equation for the non-rotating C -metric which encompass massless Klein -Gordon field, neutrino field, Maxwell field, Rarita -Schwinger field and gravitational perturbations. This equation is shown to be separable in terms of "accelerated spin weighted spherical harmonics". It is shown that, contrary to ordinary spin weighted spherical harmonics, the "accelera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…In the extremal case (r p = r m ) the point y = −1/Ar p is in general irregular singular point, and, thus, the asymptotic behaviour is difficult to investigate. But, in the case of static and axisymmetric configurations y = −1/Ar p becomes regular singular point, and the exponents then depend on the eigenvalues Λ (S) (l0) , which we found in [3] to be…”
Section: Radial Functionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the extremal case (r p = r m ) the point y = −1/Ar p is in general irregular singular point, and, thus, the asymptotic behaviour is difficult to investigate. But, in the case of static and axisymmetric configurations y = −1/Ar p becomes regular singular point, and the exponents then depend on the eigenvalues Λ (S) (l0) , which we found in [3] to be…”
Section: Radial Functionmentioning
confidence: 74%
“…The pioneering work on the separability of the Teukolsky master equation on the C -metric background has been done in [1] and generalized to the rotating case in [2]. In the preceding paper [3] we independently tackled the same problem and provided a separation for the "extreme" Newman -Penrose (NP) field components on the nonrotating C -metric background. To incorporate rotation in the C -metric is a natural generalization as some of the relativistic effects are present in rotating solutions only.…”
Section: Introductionmentioning
confidence: 99%
“…Cultures of dissociated DRG neurons represent a suitable in vitro model for the study of nerve regeneration. Several studies have been performed to understand how DRG neurons can survive and extend neurites on different substrates, and the alignment of neurites on physical patterns of micro-/ nano-dimensions have been reported (Thompson and Buettner, 2006;Sørensen et al, 2007;Kofron et al, 2009;Richardson et al, 2011;di Summa et al, 2013). It has been demonstrated that one of the most important requirements for neurons to survive is the presence of glial cells (Richardson et al, 2011;Seggio et al, 2010;Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vieira et al [121] show that for Charged massive scalar fields are considered in the gravitational and electromagnetic field produced by a dyonic black hole with a cosmic string along its axis of symmetry " exact solutions of both angular and radial parts of the covariant Klein-Gordon equation in this background can be obtained, and are given in terms of the confluent Heun functions". In [122] , Kofron separates test fields equations on the non-rotating C-metric background. He finds that the resulting equations are of the Heun or confluent Heun form for the general case.…”
Section: Some Examples Of the Heun Equation In Physical Applicationsmentioning
confidence: 99%